(untitled) (mathematica didactica, 2006)
The furtherance of presumably highly gifted children should start as early as possible, if we do not want to loose of too many kids resigning or dropping out. Yet effective furtherance in primary education requires well-prepaired tutors, a task that cannot be done in passing, neither at school nor at university. Based on own experiences at both schools and universities the author discusses problems as appear in the practices of furthering small groups of students at school (grade 2–4) as well in training tutors at university. Consequences for necessary research, for an adequate preparation of tutors and for the organisationat school conclude the article.